2016
DOI: 10.17125/plaid.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Mixer: Fostering a Diabetes Community to Support Peer Health

Abstract: Objective: Opportunities for individuals affected by type 1 diabetes (T1D) to engage in peer health activities are limited. The Diabetes Mixer is a community-based, non-clinical, face-to-face, peer health event for adults with T1D and their support person. The purpose of this paper is to 1) provide a program description of the Diabetes Mixer, and 2) analyze attendee perceptions of the Diabetes Mixer. Research Design and Method:An analysis was conducted with Diabetes Mixer attendees to understand their percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…These results are consistent with other studies examining the perspective of a community-based SSP [24]. Attending SSPs have been shown to provide numerous benefits for individuals living with diabetes, including improved glycemic control and psychosocial functioning [23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are consistent with other studies examining the perspective of a community-based SSP [24]. Attending SSPs have been shown to provide numerous benefits for individuals living with diabetes, including improved glycemic control and psychosocial functioning [23].…”
Section: Discussionsupporting
confidence: 89%
“…While there is less literature available on SSPs for individuals living with T1D, a 5-month SSP with weekly group meetings and guidance from a trained clinical psychologist decreased A1C and increased self-care activities among participants [23]. Additionally, a less formal community-based SSP for adults was evaluated and was well-received by attendees [24]. Outcomes from this SSP include building a community, forming connections due to the experience of living with T1D, and being an enjoyable environment to share resources [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We restricted our focus to studies of overall well-being, excluding articles on specific domains, such as satisfaction with college (Powless, 2012) or workplace well-being (Grawitch et al, 2018). The exception to this rule was physical well-being, which often included assessments tied to particular health contexts, such as glycemic control (e.g., Litchman, 2016).…”
Section: Conceptual Issuesmentioning
confidence: 99%
“…Likewise, using social media related positively to LGBTQ+ community members’ well-being via heightened perceived membership in groups related to their sexual identity and reduced stigma (Chong et al, 2015). In terms of people coping with medical issues, Litchman (2016) observed that more engagement in an online community corresponds with better glycemic control, an index of physical well-being. Several studies also reported the results of interventions that aided people’s ability to cope with specific medical conditions, especially the feelings of anxiety or depression surrounding those conditions (Garcia-Palacios et al, 2015; Hawkins et al, 2010; Li, 2017; P. Wang et al, 2017).…”
Section: Characterizing the Literaturementioning
confidence: 99%